2010
DOI: 10.1016/j.hrthm.2010.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Purkinje cell calcium dysregulation is the cellular mechanism that underlies catecholaminergic polymorphic ventricular tachycardia

Abstract: Background-Inherited arrhythmias can be caused by mutations in the cardiac ryanodine receptor (RyR2). The cellular source of these arrhythmias is unknown. Isolated RyR2 R4496C mouse ventricular myocytes display arrhythmogenic activity related to spontaneous Ca 2+ release during diastole. On the other hand, recent whole heart epicardial and endocardial optical mapping data demonstrate that ventricular arrhythmias in the RyR2 R4496C mouse model of CPVT originate in the His-Purkinje system, suggesting that Purkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 22 publications
(40 reference statements)
4
64
0
Order By: Relevance
“…Previous studies have demonstrated the mechanism of arrhythmia origination for BDVT and PMVT in CPVT to be abnormal calcium regulation and delayed after depolarizations (DADs). [18][19][20] Modeling studies suggest that origination and alternation of premature beats between the right and the left bundle branches of the purkinje system (the Ping-Pong mechanism) result in BDVT. When DADs arise from multiple purkinje sites, PMVT ensues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the mechanism of arrhythmia origination for BDVT and PMVT in CPVT to be abnormal calcium regulation and delayed after depolarizations (DADs). [18][19][20] Modeling studies suggest that origination and alternation of premature beats between the right and the left bundle branches of the purkinje system (the Ping-Pong mechanism) result in BDVT. When DADs arise from multiple purkinje sites, PMVT ensues.…”
Section: Discussionmentioning
confidence: 99%
“…2+ handling in cardiac Purkinje cells (P-cells) has been stimulated by growing evidence that spontaneous intracellular Ca 2+ activity accounts for abnormal Purkinje automaticity (Boyden & ter Keurs, 2001, 2005Boyden et al 2003;ter Keurs & Boyden, 2007;Hirose et al 2008b;Herron et al 2010;Kang et al 2010). Several studies re-examined normal P-cells using advanced imaging technology and highlighted unique features in the Ca 2+ mobilization of these cells (Boyden et al 2000;Cordeiro et al 2001a,b;Stuyvers et al 2005;Hirose et al 2008a).…”
Section: Recent Interest In Intracellular Camentioning
confidence: 99%
“…58 In this setting, it has been shown that delayed afterdepolarizations caused by calcium overload are a more common occurrence in Purkinje cells than in ventricular myocytes, both at baseline and after β-adrenergic stimulation. 59 The Purkinje cells are probably critical contributors to arrhythmic triggers in animal models and humans with CPVT.…”
Section: Pathophysiological Backgroundmentioning
confidence: 99%